How to Learn and Teach R / Nadiah Mohamed, Siti Noor Dina Ahmad and Mahfuzah Mahayadin - Mohamed, Nadiah; Ahmad, Siti Noor Dina; Mahayadin, Mahfuzah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
On Mac 15, 2023, the College of Computing, Informatics, and Mathematics UiTM Negeri Sembilan Kampus Kuala Pilah hosted "How to Learn and Teach R". This program gathered 50 lecturers from different fields. The KPPIM@PSPM runs this online course intending to expose professors to R software. Additionally, it is intended that this exposure would broaden the range of tools available for use in doing research in the future. Besides that, this course can boost lecturers' passion and motivation to engage in research, write, and deliver research findings at various levels. It is occasionally necessary to conduct this program to foster knowledge among academics more regularly. Positive feedback was also provided by the lecturers who participated throughout the program.